Agnatia-otocephaly complex in a low-resource setting and its implication for maternal and child health: a case report - Kubeyinje, Weyinmi E.; Udobor, Festus G.; Iweka, Reuben O.; Nwiwu, Nnejiakolam C. (International Journal of Research in Medical Sciences, 2025)
Agnatia-otocephaly complex is an extremely rare congenital fatal anomaly. This case is being reported to raise awareness of this condition and the need for sonographers to deliberately evaluate for this anomaly in patients with severe polyhydramnios in pregnancy. This allows for more effective management of this congenital anomaly. We report a 31-year-old gravida 3 para 2 who presented with complaints of difficulty with breathing and ultrasound scan findings of live fetus with severe polyhydramnios at about 34 weeks of gestation. About 2 days on admission, she spontaneously ruptured membranes and had assisted vaginal breech delivery of a live male 1.9 kg neonate who suffered early neonatal death after 20 min of active resuscitation with agnatia-otocephaly complex anomaly noticed. She was counselled on the neonatal outcome and the need for autopsy, but the parents declined. Otocephaly should be suspected in cases of fetal anomaly with polyhydramnios. In this patient, severe polyhydramnios was a presenting feature, deliberate effort could have been made to identify this congenital anomaly. It highlights the need for better training and provision of advanced tools to aid diagnosis. In this case, the neonatal outcome was fatal, and the mother suffered from respiratory distress from polyhydramnios, which could have been avoided by accurate prenatal diagnosis. Otocephaly poses a significant challenge for patients and clinicians globally, especially in low-income countries, due to its rarity, high fatality rate and complexity. This case is being reported to raise clinician awareness for proper sonographic evaluation and better management of this rare congenital disorder.